2001
DOI: 10.1021/tx010050x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Free Radicals in the Toxicity of Airborne Fine Particulate Matter

Abstract: Exposure to airborne fine particles (PM2.5) is implicated in excess of 50 000 yearly deaths in the USA as well as a number of chronic respiratory illnesses. Despite intense interest in the toxicity of PM2.5, the mechanisms by which it causes illnesses are poorly understood. Since the principal source of airborne fine particles is combustion and combustion sources generate free radicals, we suspected that PM2.5 may contain radicals. Using electron paramagnetic resonance (EPR), we examined samples of PM2.5 and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
341
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 458 publications
(358 citation statements)
references
References 35 publications
11
341
0
4
Order By: Relevance
“…There is growing recognition that the redox chemistry of organic chemical compounds plays a crucial role in the biological effect of ambient PM (Araujo et al 2008;Dellinger et al 2001;Li et al 2003aLi et al , 2003bLi et al , 2008Nel et al 2001;Squadrito et al 2001). Moreover, increased polar resolution of silica gel columns that were prior loaded with an organic DEP extract has shown that most of the redox cycling activity in the OC fraction segregates with the PAH-enriched aromatic as well as the quinone-enriched polar fractions (Li et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing recognition that the redox chemistry of organic chemical compounds plays a crucial role in the biological effect of ambient PM (Araujo et al 2008;Dellinger et al 2001;Li et al 2003aLi et al , 2003bLi et al , 2008Nel et al 2001;Squadrito et al 2001). Moreover, increased polar resolution of silica gel columns that were prior loaded with an organic DEP extract has shown that most of the redox cycling activity in the OC fraction segregates with the PAH-enriched aromatic as well as the quinone-enriched polar fractions (Li et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally Cu can cause nasal septum perforation, pulmonary granuloma, pulmonary interstitial fibrosis and lung cancer (Fang et al, 2010). It has recently been reported that heavy metals present on particles' surfaces plays a role in the generation of reactive oxygen species (ROS) (Valavanidis et al, 2000;Dellinger et al, 2001). ROS in turn could cause damage to DNA and thus induce deleterious health effects.…”
Section: Concentrations Of Pm and Heavy Metalsmentioning
confidence: 99%
“…Environmental PM is a complex mixture of particles with varying properties. How the properties of exposure to PM contribute to altered early pulmonary immune responses and dendritic cell (DC) activation in vivo are unclear but may be attributable to cellular contact-dependent particle size and surface area of the PM species, elemental and hydrocarbon constitution and an inherent ability to differentially promote oxidative stress and acute inflammation [10][11][12][13][14] .…”
mentioning
confidence: 99%